Elastoplastic Analysis of Two-Layered Circular Lining Based on the Unified Strength Theory. (2nd October 2018) - Zhang, Ning; Guo, Haomin; Khan, Tahir; Zhu, Erhao; Shi, Shaoshuai; Wu, Qingliang; Tian, Yinliang; Xie, Xiaokun
Abstract : Based on the Unified Strength Theory (UST), elastoplastic analysis of the two-layered circular lining is carried out. The stresses, displacements, and the elastic and plastic zones in both layers are discussed under different values of Young's moduli of the inner and outer layers. The results reveal that, compared to the single-layered lining, the tangential stress distributions in the two-layered linings are more reasonable along the radial direction, which is beneficial to enhance the overall elastic and plastic ultimate bearing capacities. When considering the intermediate stress (i.e., the axial load), the elastic ultimate bearing capacity will be higher. However, the plastic ultimate bearing capacity remains unchanged. Moreover, a comparison between the Unified Strength Theory and Tresca Criterion is analyzed as well.